Nickel-doped carbon nano enzyme as well as preparation method and application thereof
By hydrothermal reaction of nickel salt and cysteine under alkaline conditions, a nickel-doped carbon nanoenzyme without POD activity was developed, which solved the problem that conventional metal-doped carbon nanoenzymes were not conducive to wound healing, and achieved effective Sterilization and healing effects.
Patent Information
- Application Number
- CN202411382989.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional metal-doped carbon nanoenzymes have POD activity, which is not conducive to the healing of bacterial infection wounds later.
A nickel-doped carbon nanoenzyme was developed to form a nickel-doped carbon nanoenzyme that has no POD activity but CAT activity and SOD activity through hydrothermal reaction with cysteine under alkaline conditions.
The nickel-doped carbon nanoenzyme does not produce ROS, and uses its photothermal effect, CAT activity and SOD activity to sterilize it, which can not only achieve the sterilization effect, but also does not continuously produce ROS, reduce inflammatory response and promote wound healing.
Smart Images

Figure CN119409175A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon nanozymes, and in particular to a nickel-doped carbon nanozyme and a preparation method and application thereof. Background Art
[0002] As a new type of carbon nanomaterial, carbon quantum dots have great clinical therapeutic potential and have been widely used in biomedicine. After different functional modifications on the surface, carbon quantum dots can achieve corresponding enhancements of different effects. After surface modification (such as metal doping modification), it can achieve rapid and effective killing of bacteria through photothermal or enzyme activity. As an effective alternative to antibiotics, it has largely solved the problem of drug resistance caused by excessive use of antibiotics, provided a treatment idea for wound infections caused by bacteria, and accelerated the healing of wounds infected with bacteria.
[0003] However, most metal-doped carbon nanozymes currently have peroxidase (POD) activity and will continuously produce ROS. The large accumulation of ROS at the wound site will lead to an inflammatory response, making it difficult for skin tissue to regenerate and not conducive to the later healing of bacterial-infected wounds. Metal-doped carbon nanozyme sterilization materials without POD activity have not been reported. Summary of the invention
[0004] The problem in the prior art is that conventional metal-doped carbon nanozymes have POD activity, which is not conducive to the late healing of bacterial-infected wounds. In view of the above problems, the present invention provides a nickel-doped carbon nanozyme, which has no POD activity, CAT activity and SOD activity, and a particle size range of 50-300nm. Nickel-doped carbon nanozyme is specifically a product obtained by hydrothermal reaction of soluble nickel salt and cysteine under alkaline conditions. Under the hydrothermal conditions, metal nickel ions form coordination chemical bonds with the amino groups in cysteine.
[0005] Preferably, the soluble nickel salt includes one or a combination of two or more of nickel chloride, nickel nitrate, nickel sulfate and nickel carbonate.
[0006] Preferably, the temperature of the hydrothermal reaction is 90-200°C.
[0007] Preferably, the preparation method of the nickel-doped carbon nanozyme comprises the following steps:
[0008] Cysteine and soluble nickel salt are dissolved in pure water, and the molar ratio of cysteine to nickel ions is 1-10:1-10. The pH of the solution is then adjusted to alkaline, and after ultrasonic mixing, the solution is placed in a high-pressure hydrothermal reactor for hydrothermal reaction. After the hydrothermal reaction is completed, the solution is naturally cooled to room temperature, and the obtained reaction solution is subjected to solid-liquid separation to obtain a solid precipitate. The obtained solid precipitate is washed with pure water for multiple times and then freeze-dried to obtain nickel-doped carbon nanozyme.
[0009] Preferably, the pH adjuster is at least one of sodium hydroxide, sodium bicarbonate or sodium carbonate.
[0010] Preferably, the nickel-doped carbon nanozyme can be used as a sterilizing agent in bacterial wound infections or as a drug carrier for treating diseases.
[0011] The present invention has the following beneficial effects:
[0012] The nickel-doped carbon nanozyme obtained by the present invention has no POD activity, and does not produce ROS but can remove ROS. The nickel-doped carbon nanozyme uses its photothermal effect, CAT activity and SOD activity for sterilization. The nickel-doped carbon nanozyme can achieve a sterilization effect without continuously producing ROS, thereby reducing inflammatory response, promoting angiogenesis at the wound, and being more conducive to the late healing of bacterially infected wounds. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 :TEM image of NC Nanozyme-1
[0014] Figure 2 : Particle size distribution of NC Nanozyme-1.
[0015] Figure 3 : CAT activity test diagram of NC Nanozyme-1 and NC Nanozyme-2.
[0016] Figure 4 : POD activity test diagram of NC Nanozyme-1 and NC Nanozyme-6.
[0017] Figure 5 :Test results of NC Nanozyme-1's ability to scavenge ABTS free radicals.
[0018] Figure 6 :Test results of NC Nanozyme-1's ability to scavenge DPPH free radicals.
[0019] Figure 7 :NC Nanozyme-1 photothermal sterilization effect diagram. DETAILED DESCRIPTION
[0020] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.
[0021] Example 1
[0022] Weigh 0.030 g cysteine powder and 0.060 g NiCl 2 6H2 O crystals in a 50mL beaker, 30mL of pure water was added while stirring, 1M NaOH aqueous solution was added dropwise to the mixed solution while stirring, the pH of the solution was adjusted to 10, and then ultrasonicated for 15min to completely dissolve the cysteine powder in the solution, and then the obtained solution was placed in a hydrothermal high-pressure reactor, and hydrothermally reacted at 180°C for 8h. After the reaction was completed, the obtained reaction solution was centrifuged at 12000rpm for 10min to obtain a solid precipitate, the obtained solid precipitate was washed three times with pure water, and then re-dissolved with pure water, and freeze-dried to obtain nickel-doped carbon nanozyme, recorded as NC Nanozyme-1, and the test results of whether POD activity was present were as shown in the attached manual. Figure 4 As shown, the image shows that the NC Nanozyme-1 obtained in Example 1 has no POD activity.
[0023] The TEM image of NC Nanozyme-1 obtained in Example 1 is shown in the attached specification. Figure 1 As shown in the figure, it can be seen that its morphology is approximately spherical, the particle size is small (30-40nm), and the distribution is uniform.
[0024] The particle size distribution diagram of NC Nanozyme-1 obtained in Example 1 is shown in the attached manual. Figure 2 As shown in the figure, it can be seen that the average particle size of the obtained NC Nanozyme-1 is 167.8nm and the PDI value is 0.135.
[0025] The test results of the ability of NC Nanozyme-1 to scavenge ABTS free radicals obtained in Example 1 are shown in the attached manual. Figure 5 shown.
[0026] The test results of the ability of NC Nanozyme-1 to scavenge DPPH free radicals obtained in Example 1 are shown in the attached specification. Figure 6 shown.
[0027] The CAT activity of NC Nanozyme-1 obtained in Example 1 is as shown in the attached manual. Figure 3 As shown, Cys:Ni=1:1 represents NC Nanozyme-1.
[0028] The photothermal sterilization effect of NC Nanozyme-1 obtained in Example 1 is as shown in the attached manual. Figure 7 As shown, b represents NCNanozyme-1, a represents the blank control, and the image shows that NC Nanozyme-1 has a good bactericidal effect.
[0029] The photothermal sterilization test method is as follows:
[0030] Take 500 μL of 10 8CFU·mL -1 Staphylococcus aureus was mixed evenly with 100 μL of 1 mg / mL NCNanozyme-1 aqueous solution, and then incubated at 37°C for 1 hour, irradiated with a laser of 1.5 W and 808 nm for 10 minutes, and then 100 μL of the mixed solution was diluted 2000 times and spread on the plate. The spread plate was then cultured in an incubator at 37°C overnight, and the number of colonies on the plate was counted.
[0031] Example 2
[0032] Weigh 0.030 g cysteine powder and 0.118 g NiCl 2 6H 2 O crystals were placed in a 50mL beaker, and 30mL of pure water was added while stirring. A 1M NaOH aqueous solution was added dropwise to the mixed solution while stirring to adjust the pH of the solution to 10, and then ultrasonicated for 15 minutes to completely dissolve the cysteine powder in the solution. The obtained solution was then placed in a hydrothermal high-pressure reactor and subjected to a hydrothermal reaction at 180°C for 8 hours. After the reaction was completed, the obtained reaction solution was centrifuged at 12000rpm for 10 minutes to obtain a solid precipitate. The obtained solid precipitate was washed three times with pure water, and then redissolved with pure water. After freeze-drying, a nickel-doped carbon nanozyme was obtained, which was recorded as NC Nanozyme-2. The CAT activity of NC Nanozyme-2 obtained in Example 2 is as shown in the attached manual. Figure 3 As shown, the amount of nickel added in NC Nanozyme-2 is higher than that in NC Nanozyme-1. The test results show that the CAT activity of NC Nanozyme-2 is better than that of NC Nanozyme-1. In the figure, Cys:Ni=1:2 represents NC Nanozyme-2.
[0033] Example 3
[0034] Weigh 0.030 g of cysteine powder and 0.060 g of NiN 2 O 6 6H 2 O crystals were placed in a 50 mL beaker, and 30 mL of pure water was added while stirring. A 1 M NaOH aqueous solution was added dropwise to the mixed solution while stirring to adjust the pH of the solution to 10, and then ultrasonicated for 15 min to completely dissolve the cysteine powder in the solution. The obtained solution was then placed in a hydrothermal high-pressure reactor and subjected to hydrothermal reaction at 180 ° C for 8 h. After the reaction was completed, the obtained reaction solution was centrifuged at 12000 rpm for 10 min to obtain a solid precipitate. The obtained solid precipitate was washed three times with pure water, and then redissolved with pure water. After freeze-drying, the nickel-doped carbon nanozyme was obtained, which was recorded as NC Nanozyme-3.
[0035] Example 4
[0036] Weigh 0.030 g of cysteine powder and 0.060 g of NiSO 4 6H 2 O crystals were placed in a 50 mL beaker, and 30 mL of pure water was added while stirring. A 1 M NaOH aqueous solution was added dropwise to the mixed solution while stirring to adjust the pH of the solution to 10, and then ultrasonicated for 15 min to completely dissolve the cysteine powder in the solution. The obtained solution was then placed in a hydrothermal high-pressure reactor and subjected to hydrothermal reaction at 180 ° C for 8 h. After the reaction was completed, the obtained reaction solution was centrifuged at 12000 rpm for 10 min to obtain a solid precipitate. The obtained solid precipitate was washed three times with pure water, and then redissolved with pure water. After freeze-drying, the nickel-doped carbon nanozyme was obtained, which was recorded as NC Nanozyme-4.
[0037] Example 5
[0038] Weigh 0.030 g of cysteine powder and 0.060 g of NiCO 3 ·2Ni(OH) 2 ·4H 2 O crystals were placed in a 50 mL beaker, and 30 mL of pure water was added while stirring. A 1 M NaOH aqueous solution was added dropwise to the mixed solution while stirring to adjust the pH of the solution to 10, and then ultrasonicated for 15 min to completely dissolve the cysteine powder in the solution. The obtained solution was then placed in a hydrothermal high-pressure reactor and subjected to hydrothermal reaction at 180 ° C for 8 h. After the reaction was completed, the obtained reaction solution was centrifuged at 12000 rpm for 10 min to obtain a solid precipitate. The obtained solid precipitate was washed three times with pure water, and then redissolved with pure water. After freeze-drying, the nickel-doped carbon nanozyme was obtained, which was recorded as NC Nanozyme-5.
[0039] Comparative Example 1
[0040] Weigh 0.030 g cysteine powder and 0.060 g NiCl 2 6H 2 O crystals were placed in a 50 mL beaker, and 30 mL of pure water was added while stirring. After that, the solution was ultrasonicated for 15 min to completely dissolve the cysteine powder in the solution. The obtained solution was then placed in a hydrothermal high-pressure reactor and subjected to hydrothermal reaction at 180 ° C for 8 h. After the reaction was completed, the obtained reaction solution was centrifuged at 12000 rpm for 10 min to obtain a solid precipitate. The obtained solid precipitate was washed three times with pure water, and then re-dissolved with pure water. After freeze-drying, nickel-doped carbon nanozyme was obtained, which was recorded as NC Nanozyme-6. The test results of whether NC Nanozyme-6 has POD activity are shown in the attached manual. Figure 4As shown, the image shows that the NC Nanozyme-6 obtained in Comparative Example 1 has POD activity.
[0041] The nickel-doped carbon nanozymes obtained in Examples 1-5 and Comparative Example 1 were tested for POD activity, CAT activity, and the ability to scavenge ABTS free radicals and DPPH free radicals, and the specific test results are shown in Table 1.
[0042] in,
[0043] The test method for catalase (CAT) activity is as follows:
[0044] The carbon nanozymes obtained in Examples 1 to 5 of the present invention and Comparative Example 1 were immersed in the same volume of 100 mM H 2 O 2 In the aqueous solution, observe whether bubbles are generated in the solution. If there are no bubbles, it proves that the material has no CAT activity. On the contrary, the more bubbles are generated in the solution, the more it proves that the material catalyzes H 2 O 2 Produce O 2 The stronger the ability, the stronger the CAT activity of the material.
[0045] The test method for peroxidase (POD) activity is as follows:
[0046] The carbon nanozymes obtained in Examples 1 to 5 of the present invention and Comparative Example 1 were added to the same volume of H2O2 at a concentration of 100 mM. 2 O 2 Six test solutions were obtained from the aqueous solution. The same mass of 3,3',5,5'-tetramethylbenzidine (TMB) was added to each test solution. After standing at room temperature for 20 minutes, the six test solutions were tested for full-wavelength ultraviolet absorption at 650nm.
[0047] The test principle is: if the material has POD activity, it will catalyze H 2 O 2 A large number of hydroxyl radicals are generated. 3,3',5,5'-tetramethylbenzidine (TMB) in the test solution is oxidized to ox-TMB after combining with hydroxyl radicals. Ox-TMB has a characteristic ultraviolet absorption peak at 650nm. If the material has no POD activity, it cannot catalyze H 2 O 2 A large number of hydroxyl radicals are generated, no ox-TMB is generated in the test solution, and no UV characteristic absorption peak appears at 650nm.
[0048] The test method for the ability to scavenge ABTS free radicals is as follows:
[0049] The same mass of the carbon nanozymes obtained in Examples 1-5 of the present invention and Comparative Example 1 were added to ABTS working solutions of the same volume and concentration, respectively. After standing at room temperature for 20 minutes, the six test solutions were detected for ultraviolet wavelength absorption at 734 nm.
[0050] The test principle is: 2,2-azino-bis-(3-ethylbenzodihydrothiazoline-6-sulfonic acid) diammonium salt reacts with potassium persulfate to generate a blue-green free radical ABTS. + , the obtained free radical ABTS· + There is ultraviolet characteristic absorption at a wavelength of 734nm. After the free radical is acted upon by an antioxidant, the antioxidant gives out electrons and reacts with the free radical ABTS· + The binding will make the solution lighter in color, and the absorbance at a wavelength of 734nm will decrease or disappear.
[0051] The ABTS working solution is prepared by dissolving ABTS (2,2'-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid) in methanol, then adding potassium persulfate aqueous solution (completely dissolved by ultrasonication), mixing evenly, and placing at room temperature away from light for 12 hours to obtain the ABTS working solution.
[0052] The test method for the ability to scavenge DPPH free radicals is as follows:
[0053] The same mass of carbon nanozymes obtained in Examples 1-5 of the present invention and Comparative Example 1 were added to the same volume and concentration of DPPH alcohol solution to obtain 6 test solutions, which were allowed to stand at room temperature for 20 minutes, and the 6 test solutions were detected for characteristic absorption at 519 nm. The DPPH alcohol solution is a uniform solution formed by dissolving DPPH in methanol.
[0054] The test principle is: DPPH alcohol solution is purple, DPPH has characteristic absorption at 519nm. It is known that when antioxidants are present, DPPH free radicals are scavenged, the solution color becomes lighter, and the wavelength absorption of DPPH at 519nm decreases or disappears.
[0055] Table 1
[0056]
[0057] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A nickel-doped carbon nanozyme, characterized in that: No POD activity, but has CAT activity.
2. The nickel-doped carbon nanozyme according to claim 1, characterized in that: The particle size range is 50-300nm.
3. The nickel-doped carbon nanozyme according to claim 1, characterized in that: It also has SOD activity.
4. The nickel-doped carbon nanozyme according to claim 1, characterized in that: It is a product obtained by hydrothermal reaction of soluble nickel salt and cysteine under alkaline conditions. Under the hydrothermal conditions, metal nickel ions form coordination chemical bonds with the amino groups in cysteine.
5. The nickel-doped carbon nanozyme according to claim 4, characterized in that: The soluble nickel salt includes one or a combination of two or more of nickel chloride, nickel nitrate, nickel sulfate and nickel carbonate.
6. The nickel-doped carbon nanozyme according to claim 4, characterized in that: The temperature of the hydrothermal reaction is 90-200°C.
7. The nickel-doped carbon nanozyme according to claim 4, characterized in that: The preparation method comprises the following steps: Cysteine and soluble nickel salt are dissolved in pure water, and the molar ratio of cysteine to nickel ions is 1-10:1-10. The pH of the solution is then adjusted to alkaline, and after ultrasonic mixing, the solution is placed in a high-pressure hydrothermal reactor for hydrothermal reaction. After the hydrothermal reaction is completed, the solution is naturally cooled to room temperature, and the obtained reaction solution is subjected to solid-liquid separation to obtain a solid precipitate. The obtained solid precipitate is washed with pure water for multiple times, redissolved in pure water, and then freeze-dried to obtain nickel-doped carbon nanozyme.
8. The nickel-doped carbon nanozyme according to claim 7, characterized in that: The pH adjuster is at least one of sodium hydroxide, sodium bicarbonate or sodium carbonate.
9. A method for treating bacterial wound infection, characterized in that: A nickel-doped carbon nanozyme as described in any one of claims 1 to 8 is used as a sterilizing agent.
10. A drug treatment method, characterized in that A nickel-doped carbon nanozyme as described in any one of claims 1 to 8 is used as a drug carrier.